The effect of resistant-starch subsituted loaf bread on blood glucose level - Matapaja, Maurice Santos (2002)
Resistant starch (Hi-maizeTM) was incorporated at 11% of the total weight of the loaf bread. Sensory evaluation and proximate analysis were done to test the product's acceptability and composition. The resistant starch (RS)-substituted loaf bread was 11.6%. An in-vivo study was conducted to determine the blood glucose responses after the ingestion of the RS-substituted and the control bread. The two types of bread were fed randomly to twelve normal human subjects. Fingerpick blood samples were drawn from each subject before ingestion and at 15, 30, 45, 60 and 90 minutes after ingestion of the food samples. Blood glucose analysis was done using the glucose oxidase method. Glucose responses were significantly higher at all time intervals after ingestion of the RS-substituted bread according to t-test for paired comparison at 95% level of confidence. Areas under the glucose curve were also greater for the RS-substituted bread than for the control. Ingestion of RS-substituted bread was expected to result in reduced glucose responses but analysis showed otherwise. There may have been errors encountered during the study however, formulation and production techniques may be the primary factors.